Viscosity and Interfacial Tension of Binary Mixtures Consisting of Linear, Branched, Cyclic, or Oxygenated Hydrocarbons with Dissolved Gases Using Surface Light Scattering and Equilibrium Molecular Dynamics Simulations - Klein, Tobias; Lenahan, Frances; Zhai, Ziwen; Kerscher, Manuel; Jander, Julius Hans; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Thermophysics, 2022)
In the present study, the influence of the molecular characteristics of the solvent and solute on the dynamic viscosity and interfacial tension of binary mixtures consisting of a liquid with a dissolved gas is investigated using surface light scattering (SLS) and equilibrium molecular dynamics (EMD) simulations. In detail, binary mixtures consisting of linear, branched, cyclic, or oxygenated hydrocarbons and the solutes hydrogen, helium, methane, water, carbon monoxide, or carbon dioxide are studied in the temperature range between (298 and 573) K and for solute mole fractions up to 0.2. With SLS, the liquid dynamic viscosity and interfacial tension of the binary mixtures could be accessed in macroscopic thermodynamic equilibrium with average expanded uncertainties (coverage factor k = 2) of (2.4 and 2.3)%, respectively. While EMD simulations were able to predict the influence of the dissolved gases on the interfacial tension of the binary mixtures, the simulations fail to represent the influence of the dissolved gas on the viscosity. Due to the systematic variation of the solvent and solute molecules, the influence of the molecular characteristics, e.g., in the form of size, shape, or polarity, on the thermophysical properties of the mixtures is discussed. Dissolving carbon dioxide, e.g., leads to a reduction of both properties by up to 60% compared to the properties of the pure solvent. Dissolved helium, on the other hand, has only a small influence on the properties of the pure solvent. The influence of dissolved water was found to be negligible in mixtures with an alkane but strongly increases both properties when dissolved in an alcohol, which may be explained by the formation of hydrogen bonds.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Binary mixtures; Gases; Hydrocarbons; Interfacial tension; Molecular dynamics simulations; Surface light scattering; Viscosity